Peran ekonomi digital terhadap hubungan ASEAN-Korea Free Trade Area (AKFTA) - Ghina Fitri Ariesta Susilo; Utpala Rani (Jurnal Ekonomi Modernisasi, 2020)
This study is a qualitative desk research that examines the role of the digital economy in the ASEAN-Korea Free Trade Area (AKFTA) relations. ASEAN and Korea pay attention to the development of the 4.0 revolution and form the ASEAN-Korea Free Trade Area (AKFTA) to establish mutually beneficial relations. The development of the 4.0 industrial revolution has the potential to increase the level of global income and improve the quality of life of populations around the world. The success of the Korean industry can provide very valuable lessons for ASEAN by inspiring this group of countries to implement a digital economy. The partnership reflects the potential benefits of industrial improvement through digitalization and automation, the ASEAN-Republic of Korea Cooperation Center has implemented several trade and investment programs in industry segments related to Industry 4.0. AKFTA will enhance the international competitiveness of ASEAN and Korea by promoting the competition and efficiency that both parties have. AKFTA will shift the trade balance to ASEAN encourage rapid growth of the digital economy and give positive impacts to both parties.